TEACHER REINFORCEMENT TO THE STUDENTS TO UNDERSTAND THE SIX ENGLISH TENSES - Andi Masriadi Tarmin; Nirwana Darwis; Hasriati Nur (International Journal of Research on English Teaching and Applied Linguistics, 2022)
This thesis presents research about “Teacher Reinforcement to the Students to Understand the Six English Tenses at the Tenth Grade of Sma Islam Athirah Bone”, the students always find the difficulties in their tenses understanding. Reinforcement method is one of methods which can help the students to solve their difficulties in their tenses understanding. The problem statements of this thesis is: does the use of reinforcement effective to the student understand the six tenses at the tenth grade students of Sma Islam Athirah Bone. This research uses quantitative method with pre-experimental design. The researcher applies cluster sampling by choosing IPS class of the first year that consists of 27 students with one group pre-test and post-test design. This research employs a test based on the problem statement investigated, it is multiple choice  test. Multiple choice test consists of pre-test was given to the students to know the students’ tenses understanding before applying reinforcement method and post-test is given to the students to know the students’ tenses understanding after applying reinforcement method, while the data obtains through tests are analyzed with mean score and the formula of t-test. After several meetings, this research finds out the use of reinforcement method is sigificantly effective in increasing the students tenses understanding. The result of this research shows : (1) the mean score obtained by the students through pre-test is 41,03 and post-test is 54,11. (2) the t-test value is higher than the t-table (10,052.048). It means that there is a significant difference between the result of the students’ pre-test and post-test. Therefore,  null hypothesis (H0) is rejected and alternative hypothesis (H1) is accepted.